Relationship Between RNF213 p.R4810K and Echocardiographic Findings in Patients with Cerebrovascular Diseases: A Multicenter Prospective Cohort Study - Kotaro Noda; Yorito Hattori; Tatsuya Nishii; Hiroki Horinouchi; Yuriko Nakaoku; Soshiro Ogata; Yasunobu Inagaki; Ryotaro Asano; Takeshi Yoshimoto; Kunihiro Nishimura; Takeshi Ogo; Yoshikazu Nakaoka; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background RING finger protein 213 (RNF213) p.R4810K is an established risk factor for moyamoya disease and intracranial artery stenosis in East Asian people. Recent evidence suggests its potential association with extracranial cardiovascular diseases, including pulmonary hypertension. We hypothesized that insidious abnormal cardiac functions are detected in RNF213 p.R4810K carriers with cerebrovascular diseases. Methods and Results We investigated patients registered in the National Cerebral and Cardiovascular Center Genome Registry between May 2017 and August 2021 who underwent echocardiography. All patients had cerebrovascular diseases. Patients with a medical history of chronic heart or pulmonary diseases were excluded. RNF213 p.R4810K was genotyped in all the patients. Of 2089 patients registered in the registry, 71 carriers and 1241 noncarriers were eligible for our analyses. The carriage of RNF213 p.R4810K emerged as a significant predictor for longer right ventricular outflow tract acceleration time in multivariable linear regression analysis (β=8.33 [95% CI, 0.92–15.74]; P=0.028). Additionally, the carriers showed increased odds of having right ventricular outflow tract acceleration time values ≥150 milliseconds (odds ratio, 2.22 [95% CI, 1.18–4.18]; P=0.014) in multivariable logistic regression analysis. Conclusions A longer right ventricular outflow tract acceleration time may reflect an increased pulmonary vascular bed induced by abnormal vascular collateral networks and dilation of capillary vessels in peripheral pulmonary arteries in the preclinical stage of RNF213‐related pulmonary hypertension. Thus, the right ventricular outflow tract acceleration time marker in RNF213 p.R4810K carriers suggests a biphasic course from the presymptomatic to symptomatic phase. Furthermore, vascular neurologists should carefully examine multiple organs because RNF213‐related vasculopathy covers systemic cardiovascular diseases. Registration URL: https://www.umin.ac.jp; Unique identifier: UMIN000050750.